PERSPEKTIF PUSTAKAWAN DALAM PENGARUH PENATAAN KOLEKSI (SHELVING) TERHADAP SISTEM TEMU KEMBALI INFORMASI DI UPT PERPUSTAKAAN POLITEKNIK NEGERI SRIWIJAYA - Rohmaniyah, Rohmaniyah; Prastiwi, Anggun (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze librarians' perspectives on the influence of collection shelving on the effectiveness of the information retrieval system at the Sriwijaya State Polytechnic Library. Collection shelving is a fundamental activity in library management that serves to facilitate users in efficiently retrieving library materials. This study uses a qualitative descriptive approach with data collection through observation, interviews, and documentation. The results show that librarians consider good collection shelving to have a significant impact on the speed and accuracy of information retrieval. However, there are still obstacles such as limited human resources, inconsistency in shelving activities, and low awareness among library users in maintaining the tidiness of the shelves. Therefore, more effective collection shelving strategies and continuous education for users are needed so that the information retrieval process can be optimized.